Challenges and Coping Strategies of Non-Education Graduate Mathematics Teachers in Senior High School: A Phenomenological Approach - Rodriguez, Gladys M.; Andrade, Rose R. (Future Science / FSH-PH Publications, 2025)
This study explores the challenges and coping strategies of non-education graduate Mathematics teachers in senior high school, an area that has received limited attention. Using a phenomenological research design, the study examined the experiences of ten non-education graduate Mathematics teachers from a senior high school in the Philippines. Data were gathered through semi-structured interviews and analyzed thematically. The findings revealed challenges in classroom management, selecting appropriate teaching strategies, subject knowledge, and perceived stigma. Teachers employed strategies such as peer support, professional development, resourcefulness, and a strong passion for teaching to address these challenges. To strengthen the pedagogical capacity of non-education graduate Mathematics teachers, institutions must offer targeted professional development, structured mentorship, and classroom management support, alongside opportunities for advanced studies and formal recognition to foster sustained growth and effectiveness.